Estrategias Efectivas en Programas de Alfabetización Mediática contra la Desinformación Digital - Monica Niño Romero (Journal of Digital Media & Interaction)
In the digital age, misinformation represents a growing challenge to information integrity and democracy, exacerbated by the rapid spread of fake news on digital platforms. This study examines the effectiveness of media literacy education programs implemented in Europe and Latin America, targeting different groups such as youth, the elderly and vulnerable communities. Through a mixed methodological approach, including literature review, content analysis and questionnaires to journalists, key factors in the design and implementation of literacy initiatives were identified. The findings highlight the effectiveness of adapted methodologies, such as social network simulations for young people and face-to-face workshops for older adults, in improving critical skills in the face of misinformation. However, challenges remain in the inclusion of marginalized communities and in the technological training of journalists, who consider algorithmic literacy essential to confront information manipulation. This article concludes that media literacy programs, combined with regulatory frameworks and inter-institutional collaboration, are fundamental tools for building an informed and resilient citizenry in the face of the risks of the digital society.